Life Prediction of Desert Sand PVA-ECC in Salt Freezing Environment. Issue 1 (September 2020) - Huifang, Hou; Min, Yan
Abstract: In order to predict the life of Desert Sand PVA-ECC in chloride environment and freeze-thaw cycle coupling, the average influence value (MIV) method was used to screen the input variables of the prediction model. Finally, the fiber volume, fly ash, silica fume and freeze-thaw cycles are selected as input variables, and the "4-13-1" error reverse transmission neural network model with relative dynamic elastic modulus as the output value is established. Finally, the GA-BP neural network is used to predict the life of the specimens which have not been destroyed by 300 freeze-thaw cycles. Finally, the best fiber volume fraction of salt freeze resistant life is 1%. Only after 475 freeze-thaw cycles.